Synchronization network of data models in the process industry - Rahm, Julian; Henselmann, Daniel; Urbas, Leon (IEEE International Conference on Emerging Technologies and Factory Automation, ETFA, 2021)
In the process industry, ongoing digitization is leading to a considerable information exchange over the entire life cycle of a process plant. Data models are usually created in the initial planning phases and these change continuously with further progress including the planning phase itself, plant adaptations after commissioning, and maintenance. The various models from the disciplines involved have a considerable semantic overlap, creating dependencies. Changes in one model inevitably lead to changes in another. This paper presents an approach for networking and synchronization between data models based on these overlaps. The resulting synchronization network provides models which are as free of inconsistencies as possible across different disciplines at any point in time. In addition, first approaches for collaborative conflict resolution are presented. Approaches from model-driven software development and web technologies are adapted to the application domain of the process industry. Typical information models created during the planning phase of a process engineering plant serve as an example.
Created from Fastlane, Scopus look-up
Keywords: Consistency; Dexpi; Model transformation; Mtp; Ne150; Ne159; Roundtrip engineering; Synchronisation network; Synchronization; Triple graph grammar